2007
DOI: 10.1248/jhs.53.177
|View full text |Cite
|
Sign up to set email alerts
|

Optical Resolution and Absolute Configuration of Branched 4-Nonylphenol Isomers and Their Estrogenic Activities

Abstract: To determine the effects of optical isomerism on the estrogenic activity of 4-nonylphenol (NP) isomers, four optically active NP isomers, (3R)-4-(3-ethyl-2-methylhexan-2-yl)phenol, (3S )-4-(3-ethyl-2-methylhexan-2-yl)phenol, (4R)-4-(2,4-dimethylheptan-4-yl)phenol and (4S )-4-(2,4-dimethylheptan-4-yl)phenol, were prepared and separated using chiral HPLC. Their absolute configurations were elucidated by X-ray crystallographic analysis of their bromobenzoylated derivatives. The estrogenic activities (recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
(26 reference statements)
0
7
0
1
Order By: Relevance
“…Many publications have now been published dealing with the environmental occurrence and ecotoxicology of C(2)À ÀO(1)À ÀC (6) 105.55(9) O(10)À ÀC(10)À ÀC(6) 126.69(11) O(2)À ÀC(2)À ÀO (1) 121.31(11) O(11)À ÀC(10)À ÀC(6) 108.12(10) O(2)À ÀC(2)À ÀC (3) 130.87(11) C(10)À ÀO(11)À ÀC(12) 119.47(9) O(1)À ÀC(2)À ÀC (3) 107.79(9) C(13)À ÀC(12)À ÀC(17) 121.85(11) C(2)À ÀC(3)À ÀC(31) 114.50(10) C(13)À ÀC(12)À ÀO(11) 118.31(12) C(2)À ÀC(3)À ÀC (4) 102.73(10) C(17)À ÀC(12)À ÀO(11) 119.62(11) C(31)À ÀC(3)À ÀC (4) 116.01(11) C(12)À ÀC(13)À ÀC (14) 118.64(12) C(2)À ÀC(3)À ÀC (7) 99.33(9) C(13)À ÀC(14)À ÀC (15) 121.76(12) C(31)À ÀC(3)À ÀC (7) 119.23(11) C(16)À ÀC(15)À ÀC (14) 117.35(11) C(4)À ÀC(3)À ÀC (7) 102.43(9) C(16)À ÀC(15)À ÀC(18) 123.18(11) C(5)À ÀC(4)À ÀC (3) 103.69(9) C(14)À ÀC(15)À ÀC (18) 119.42(11) C(6)À ÀC(5)À ÀC (4) 101.54(9) C(17)À ÀC(16)À ÀC (15) 121.59(12) O(1)À ÀC(6)À ÀC (10) 108.10(9) C(12)À ÀC(17)À ÀC (16) 118.70(11) O(1)À ÀC(6)À ÀC (5) 105.54(9) C(20)À ÀC(18)À ÀC (15) 112.36(10) C(10)À ÀC(6)À ÀC (5) 115.35(10) C(20)À ÀC(18)À ÀC (19) 108.27(11) O(1)À ÀC(6)À ÀC (7) 102.43(9) C(15)À ÀC(18)À ÀC (19) 106.32(10) C(10)À ÀC(6)À ÀC (7) 119.46(10) C(20)À ÀC(18)À ÀC (21) 110.58(10) C(5)À ÀC(6)À ÀC (7) 104.44(10) C(15)À ÀC(18)À ÀC (21) 108.39(10) C(8)À ÀC(7)À ÀC (9) 109.27(11) C(19)À ÀC(18)À ÀC (21) 110.85(10) C(8)À ÀC(7)À ÀC (6) 115.35(10) C(22)À ÀC(21)À ÀC(23) 110.32(11) C(9)À ÀC(7)À ÀC (6) 113.06(11) C(22)À ÀC(21)À ÀC (18) 112.04(11) C(8)À ÀC(7)À ÀC (3) 113.77(10) C(23)À ÀC(21)À ÀC (18) 114.53(10) C(9)À ÀC(7)À ÀC…”
Section: Ecotoxicological Implicationsunclassified
See 1 more Smart Citation
“…Many publications have now been published dealing with the environmental occurrence and ecotoxicology of C(2)À ÀO(1)À ÀC (6) 105.55(9) O(10)À ÀC(10)À ÀC(6) 126.69(11) O(2)À ÀC(2)À ÀO (1) 121.31(11) O(11)À ÀC(10)À ÀC(6) 108.12(10) O(2)À ÀC(2)À ÀC (3) 130.87(11) C(10)À ÀO(11)À ÀC(12) 119.47(9) O(1)À ÀC(2)À ÀC (3) 107.79(9) C(13)À ÀC(12)À ÀC(17) 121.85(11) C(2)À ÀC(3)À ÀC(31) 114.50(10) C(13)À ÀC(12)À ÀO(11) 118.31(12) C(2)À ÀC(3)À ÀC (4) 102.73(10) C(17)À ÀC(12)À ÀO(11) 119.62(11) C(31)À ÀC(3)À ÀC (4) 116.01(11) C(12)À ÀC(13)À ÀC (14) 118.64(12) C(2)À ÀC(3)À ÀC (7) 99.33(9) C(13)À ÀC(14)À ÀC (15) 121.76(12) C(31)À ÀC(3)À ÀC (7) 119.23(11) C(16)À ÀC(15)À ÀC (14) 117.35(11) C(4)À ÀC(3)À ÀC (7) 102.43(9) C(16)À ÀC(15)À ÀC(18) 123.18(11) C(5)À ÀC(4)À ÀC (3) 103.69(9) C(14)À ÀC(15)À ÀC (18) 119.42(11) C(6)À ÀC(5)À ÀC (4) 101.54(9) C(17)À ÀC(16)À ÀC (15) 121.59(12) O(1)À ÀC(6)À ÀC (10) 108.10(9) C(12)À ÀC(17)À ÀC (16) 118.70(11) O(1)À ÀC(6)À ÀC (5) 105.54(9) C(20)À ÀC(18)À ÀC (15) 112.36(10) C(10)À ÀC(6)À ÀC (5) 115.35(10) C(20)À ÀC(18)À ÀC (19) 108.27(11) O(1)À ÀC(6)À ÀC (7) 102.43(9) C(15)À ÀC(18)À ÀC (19) 106.32(10) C(10)À ÀC(6)À ÀC (7) 119.46(10) C(20)À ÀC(18)À ÀC (21) 110.58(10) C(5)À ÀC(6)À ÀC (7) 104.44(10) C(15)À ÀC(18)À ÀC (21) 108.39(10) C(8)À ÀC(7)À ÀC (9) 109.27(11) C(19)À ÀC(18)À ÀC (21) 110.85(10) C(8)À ÀC(7)À ÀC (6) 115.35(10) C(22)À ÀC(21)À ÀC(23) 110.32(11) C(9)À ÀC(7)À ÀC (6) 113.06(11) C(22)À ÀC(21)À ÀC (18) 112.04(11) C(8)À ÀC(7)À ÀC (3) 113.77(10) C(23)À ÀC(21)À ÀC (18) 114.53(10) C(9)À ÀC(7)À ÀC…”
Section: Ecotoxicological Implicationsunclassified
“…Unfortunately, due to the difficulty in obtaining pure enantiomers of the chiral NP isomers, the enantiomeric effects of chiral NP isomers on the estrogenic activity are still not well known. Recently, Saito et al 16 reported enantioselective resolution of two racemic NP isomers using HPLC and elucidation of the absolute structure by X-ray crystallographic analysis of their bromobenzoylated derivatives. The estrogenic activities of these enantiomers were tested by recombinant yeast screen assay, and no difference between the enantiomers and their corresponding racemates was found.…”
Section: Introductionmentioning
confidence: 99%
“…Nonylphenol (NP) with molecular formula C 6 H 4 -(OH)C 9 H 19 has marked its place in many industrial applications, like the preparation of lubricating oil additives, plasticizers, antioxidants for rubbers and plastics, starting material for the production of surfactants and phenolic resins. During commercial preparation several isomeric forms of NP were observed and grouped using their mass spectra [14][15][16]. The nonylphenol isomers differ in two ways: (1) position of the alkyl side chain attached to the phenol ring and (2) the degree of branching in the side chain.…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, known that the biological activity of chiral phenols depends substantially on the configuration of their chiral cen ters [5][6][7].…”
Section: Introductionmentioning
confidence: 99%